Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Putu Annet Cahaya Putri; Putu Ngurah Suyatna Yasa; Luh Putu Lusi Satyandarini Surya (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2022)
Good Corporate Governance is one of the systems and policies in regulating financial performance to achieve the success of banking companies. Assisted by Corporate Social Responsibility is used as a strategic step in developing financial performance to attract investors. The purpose of the study is to find out if there is a link between Good Corporate Governance and Corporate Social Responsibility which has implications for the financial performance of companies, especially banking. There are as many as 43 banking companies listed on the Indonesia Stock Exchange 2018-2020 so that the population is mentioned in this study. Sampling methods are using samples with certain criteria or often called purposive sampling, which amounted to 114 samples. The data source is in the form of annual reports of secondary data obtained on the Indonesia Stock Exchange website. The analysis technique is multiple linear regression. With this analysis, the results of both free variables significantly have simultaneous and partial effect on bound variables. From these results, this means that the more number and existence of good corporate governance mechanisms, the company's financial performance increases. In Corporate Social Responsibility activities, there are also more and more indicator disclosures than Corporate Social Responsibility activities in a company, its financial performance will also improve and vice versa.